KESANTUNAN BERBAHASA ORANGTUA DAN ANAK DALAM LINGKUNGAN KELUARGA DESA ORHILI SUSUA - Ferilia Laia (Universitas Nias Raya, 2024)
This research is motivated by language politeness between parents and children in the family environment of Orahili Susua village. The aim of this research is to describe the form of language politeness between parents and children in the family environment in Orahili Susua village. This type of research uses case study research. Case study research is an in-depth exploration of a limited system based on extensive data collection. Based on the research findings and discussion, the result was that politeness in the language of parents and children in Orahili Susua village found 42 utterances, consisting of several maxims: (1) maxim of wisdom 15 utterances (2) maxim of generosity 10 utterances (3) maxim of respect 4 utterances (4) maxim of simplicity 6 utterances (5) maxim of consensus 5 utterances (6) maxim of sympathy 2 utterances. The conclusions from this research show that the speech of parents and children in the Orahili Susua village family environment complies with the principles of language politeness. There are also those who violate the principles of politeness in 10 utterances, consisting of: (1) maxim of wisdom 2 utterances, (2) maxim of respect 4 utterances, (3) maxim of consensus 4 utterances. For this reason, it is hoped that future researchers will further develop this research to provide benefits to readers.